Trenchant microbiological-based approach for the control of Striga: Current practices and future prospects - Olowe, Olumayowa Mary; Akanmu, Akinlolu Olalekan; Ayangbenro, Ayansina Segun; Fadiji, Ayomide Emmanuel; Bitire, Tope Daniel; Odhiambo, Jude J. O.; Kutu, Funso Rahael; Babalola, Olubukola Oluranti (Frontiers in Sustainable Food Systems, 2023)
Striga species are obligate parasitic weeds most of which are members of the Orobanchaceae family. They are commonly associated with staple crops and constitute threats to food security, especially in Sub-Saharan Africa. They pose deleterious impacts on staple cereal crops like maize and pearl millet, resulting in 7-10 billion dollars yield losses or, in extreme infestations, entire crop losses. Farmers’ limited knowledge about the weed (genetics, ecology, nature of the damage caused, complex life cycle, interactions with its host and associated microbes) and their attitude towards its control have negatively affected its management and sustainability. With the present Striga management such as mechanical, chemicals, cultural and biological measures, it is extremely difficult to achieve its active management due to nature of the association between host plants and parasites, which requires highly selective herbicides. The use of soil microbes has not been well explored in the management of Striga infection in African countries. However, many soil microorganisms have been considered viable biological control techniques for fighting parasitic weeds, due to their vast action and roles they play in the early stage of host-Striga interaction. Their application for pest control is well perceived to be cost-effective and eco-friendly. In this review, we gave a comprehensive overview of major knowledge gaps and challenges of smallholders in Striga management and highlighted major potentials of microbial-based approach with respect to the mechanisms of host-Striga-microbe interactions, and the metagenomics roles on Striga management that include understanding the microbe and microbial systems of Striga-infested soil.